2021
DOI: 10.1136/bmjgh-2020-004547
|View full text |Cite
|
Sign up to set email alerts
|

One hundred thirty-three observed COVID-19 deaths in 10 months: unpacking lower than predicted mortality in Rwanda

Abstract: The African region was predicted to have worse COVID-19 infection and death rates due to challenging health systems and social determinants of health. However, in the 10 months after its first case, Rwanda recorded 10316 cases and 133 COVID-19-related deaths translating to a case fatality rate (CFR) of 1.3%, which raised the question: why does Rwanda have a low COVID-19 CFR? Here we analysed COVID-19 data and explored possible explanations to better understand the disease burden in the context of Rwanda’s infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Though the COVID-19 pandemic hit, directly and indirectly, the vital health services on the continent (15), unexpectedly, Africa has not yet experienced the predicted large burden of COVID-19 (16)(17)(18). As of 4 September 2021, the entire continent has reported a toll of approximately 8 million cases and 200,000 deaths, 3.6% and 4.4% of the global figures, respectively, despite the African population is about 16% of the worldwide population.…”
Section: Introductionmentioning
confidence: 99%
“…Though the COVID-19 pandemic hit, directly and indirectly, the vital health services on the continent (15), unexpectedly, Africa has not yet experienced the predicted large burden of COVID-19 (16)(17)(18). As of 4 September 2021, the entire continent has reported a toll of approximately 8 million cases and 200,000 deaths, 3.6% and 4.4% of the global figures, respectively, despite the African population is about 16% of the worldwide population.…”
Section: Introductionmentioning
confidence: 99%
“…On September 2, 2021, mortality related to COVID-19 was still limited to 1,105 people (RBC, n.d.). This low overall mortality rate has been noted throughout the pandemic, with previous reports showing that Rwanda only observed 133 COVID-19 deaths in the ten months after its first COVID-19 case (Musanabaganwa et al, 2021). Africa in general observed a lower mortality ratio compared to the rest of the world, with 168 deaths per million people, whereas the ratio is 402, 2160 and 2739 per million in South-East Asia, Europe, and Northern America, respectively Dashboard, n.d.).…”
Section: Introductionmentioning
confidence: 54%
“…The knowledge of mask use to prevent COVID-19 infection was not included in the definition of this composite outcome due to the inconsistencies in the global literature regarding its benefits at the time of the survey. 29 In Rwanda, while mandatory use of masks in public premises was communicated on 19 April, 2020, 30 nation-wide implementation of facemasks only started after the national lockdown was relaxed on 4 May, 2020 21when data collection for this study was almost concluded. However, we did assess how the proportion of participants with good knowledge about COVID-19 changed when we included covering one's mouth and nose with a cloth/mask as part of the outcome definition.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%